A histological continuum between dentinogenesis imperfecta and dentin dysplasia: A case report with literature review - Nikita Gulati; Saurabh Juneja; Akriti Singh; Iqbal Singh (Wolters Kluwer Medknow Publications, 2019)
Dentinogenesis Imperfecta and dentin dysplasia are genetic oral diseases inherited in a simple autosomal dominant mode, with high penetrance and a low mutation rate. Both of them are present with bulbous crowns, marked cervical constrictions, severe attritions, few periapical radiolucencies, and premature tooth loss. The diagnosis is based on family history, and detailed clinical examination, while genetic diagnosis may become useful in the future once sufficient disease-causing mutations have been discovered. Here, we present a case with overlapping features of both dentinogenesis imperfecta and dentin dysplasia asserting both the anomalies to be part of the same continuum of the genetic event.